1998
DOI: 10.2307/2463521
|View full text |Cite
|
Sign up to set email alerts
|

Noise and Nonlinearity in Measles Epidemics: Combining Mechanistic and Statistical Approaches to Population Modeling

Abstract: We present and evaluate an approach to analyzing population dynamics data using semimechanistic models. These models incorporate reliable information on population structure and underlying dynamic mechanisms but use nonparametric surface-fitting methods to avoid unsupported assumptions about the precise form of rate equations. Using historical data on measles epidemics as a case study, we show how this approach can lead to better forecasts, better characterizations of the dynamics, and a better understanding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 2 publications
0
32
0
Order By: Relevance
“…The parametric part of the model allows for a portion of the dynamics to be defined mechanistically, while the nonparametric part of the model allows for flexibility in long-term or interannual changes in a parameter of interest. Although the usefulness of semiparametric models has been recently underscored in the ecological literature (Ellner et al 1998), their application to nonlinear dynamics that are driven by long-term or interannual variation has not been recognized (with the exception of a fisheries model; A. Solow, personal communication). For the relatively long time series of disease records, gradual changes in parameter values are inevitable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The parametric part of the model allows for a portion of the dynamics to be defined mechanistically, while the nonparametric part of the model allows for flexibility in long-term or interannual changes in a parameter of interest. Although the usefulness of semiparametric models has been recently underscored in the ecological literature (Ellner et al 1998), their application to nonlinear dynamics that are driven by long-term or interannual variation has not been recognized (with the exception of a fisheries model; A. Solow, personal communication). For the relatively long time series of disease records, gradual changes in parameter values are inevitable.…”
Section: Discussionmentioning
confidence: 99%
“…We rely here on a similar semiparametric approach to develop a time series model for diseases with temporary immunity and unspecified variation in the transmission rate. Nonlinear time series models of this sort allow us to combine mechanistic representations of the processes we know with phenomenological representations of unknown processes (Ellner et al 1998). To our knowledge, this is the first attempt at using a statistical time series approach to understand retrospectively fluctuations in disease cycles as the result of both intrinsic and extrinsic factors, with the latter not limited to noise and seasonality.…”
mentioning
confidence: 99%
“…We call model a semiparametric mechanistic model. Similar approaches were introduced in Ellner et al (1998).…”
Section: 2 a Semiparametric Time Series Susceptible–infectious–recmentioning
confidence: 99%
“…To use model , we must first reconstruct the number of susceptible individuals. Ellner et al (1998) and Finkenstädt and Grenfell (2000) considered the case of non‐recurring SIR diseases like measles. This is simpler than our current problem because, once a host is infected, under the SIR mechanism they will never be reinfected.…”
Section: The Semiparametric Time Series Susceptible–infectious–recmentioning
confidence: 99%
“…Mathematical models have long been used to predict the transmission risk of airborne infectious diseases in the built environment. Epidemic modeling approaches such as susceptible-infector-susceptible (SIS) (16), susceptible-infectious-recovered (SIR) (17) competing-risks (18,19), neural network (20), and Reed-Frost (21,22) models are used to describe the progression of a disease in a population, although it is shown that these models alone cannot explain the spread of airborne infectious diseases such as measles in indoors environments (22). Therefore, epidemic models are usually combined with other mathematical approaches to predict the risks associated with indoor spaces such as airplanes, hospitals (3), schools (17), residences (23), and healthcare facilities (24).…”
Section: Introductionmentioning
confidence: 99%